Judah Halevi's Fideistic Scepticism in the Kuzari - Krinis, Ehud (Studies and Texts in Scepticism, 2020)
The book provides the first comprehensive study on Judah Halevi's use of sceptical tactics in his wrestling with the dogmatic-rationalistic trends of the Arabic culture of his period (11th- 12th centuries).